(untitled) (International Journal of Innovative Technologies in Economy, 2018)
This article contains a brief description of the contribution of the great leader Heydar Aliyev to the development of agriculture in Azerbaijan. The issues of determining the prospects for development and the formation of a new potential of agriculture during his reign are also considered. The expedient solution of agricultural problems presented by him suggests the possibility of a rapid transfer of the agrarian sector of the economy to a new level. In addition, special attention is paid to the development of the agricultural sector, its regulatory regulation and identification of further prospects for its development, and Heydar Aliyev’s special role in the development of agriculture is emphasized.